2013
DOI: 10.1117/12.2011466
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating spin-on carbon materials at low temperatures for high wiggling resistance

Abstract: Spin-on carbon (SOC) materials play an important role in the multilayer lithography scheme for the mass production of advanced semiconductor devices. One of the SOC's key roles in the multilayer process (photoresist, silicon-containing hardmask, SOC) is the reactive ion etch (RIE) for pattern transfer into the substrate. As aspect ratios of the SOC material increase and feature sizes decrease, the pattern transfer from SOC to substrate by a fluorine-containing RIE induces severe pattern deformation ("wiggling"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 3 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…However, as photoresist patterns with a high aspect ratio could easily result in a collapse of photoresist patterns, a hard-mask between the photoresist and the substrate film being etched has been introduced for the lithography and etching process, as shown in (i) of Figure 1 a. In general, this lithography and etching process using a hard-mask is followed by (i) hard-mask deposition (or spin-coating) on the substrate being etched, (ii) chemical–mechanical planarization (CMP) and cleaning, (iii) SiON layer chemical-vapor deposition (CVD) and photoresist spin coating, (iv) photoresist exposure and development, (v) SiON layer etching, (vi) hard-mask etching, (vii) photoresist strip, (viii) substrate film etching, and SiON strip [ 10 , 11 ]. Thus, the hard-mask supplies the transfer role of the photoresist patterns via anisotropic dry etchings, requiring high chemical, heat, and etching resistance.…”
Section: Introductionmentioning
confidence: 99%
“…However, as photoresist patterns with a high aspect ratio could easily result in a collapse of photoresist patterns, a hard-mask between the photoresist and the substrate film being etched has been introduced for the lithography and etching process, as shown in (i) of Figure 1 a. In general, this lithography and etching process using a hard-mask is followed by (i) hard-mask deposition (or spin-coating) on the substrate being etched, (ii) chemical–mechanical planarization (CMP) and cleaning, (iii) SiON layer chemical-vapor deposition (CVD) and photoresist spin coating, (iv) photoresist exposure and development, (v) SiON layer etching, (vi) hard-mask etching, (vii) photoresist strip, (viii) substrate film etching, and SiON strip [ 10 , 11 ]. Thus, the hard-mask supplies the transfer role of the photoresist patterns via anisotropic dry etchings, requiring high chemical, heat, and etching resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, spin-on-carbon (SOC) has attracted attention as a hard mask material for pattern transfer into Si for mass production of advanced semiconductor devices [13,14], exhibiting pattern transfer without deformation down to critical dimension (CD) 40 nm with high etch resistance and low defectivity. Previous research has also demonstrated Si fins down to 15 nm with relatively high aspect ratios using SOC for pattern transfer [15].…”
Section: Introductionmentioning
confidence: 99%
“…CO 2 , COS, O 2 , C 4 F 8 , SF 6 , Ar etc., are usually used during hard mask etching. [8][9][10] Main etching (ME) is the reaction of C 4 F 8 , C 4 F 6 , O 2 , Ar, NF 3 with SiO 2 film. [11][12][13] The fluorine plasmas (F * ) dissociated by fluorocarbons and hydrofluorocarbons can react with ARC to generate gas then volatilize.…”
mentioning
confidence: 99%